Steroid receptor coactivator-1 splice variants differentially affect corticosteroid receptor signaling - Meijer, O C; Kalkhoven, E; van der Laan, S; Steenbergen, P J; Houtman, S H; Dijkmans, T F; Pearce, D; de Kloet, E R (Endocrinology (Philadelphia), 2005)
The mechanisms of receptor- and cell-specific effects of the adrenal corticosteroid hormones via mineralo- (MRs) and glucocorticoid receptors (GRs) are still poorly understood. Because the expression levels of two splice variants of the steroid receptor coactivator-1 (SRC-1) 1a and 1e, can differ significantly in certain cell populations, we tested the hypothesis that their relative abundance could determine cell- and receptor-specific effects of corticosteroid receptor-mediated transcription. In transient transfections, we demonstrate three novel types of SRC-1a- and SRC-1e-specific effects for corticosteroid receptors. One is promoter dependence: SRC-1e much more potently coactivated transcription from several multiple response element-containing promoters. Mammalian 1-hydrid studies indicated that this likely does not involve promoter-specific coactivator recruitment. Endogenous phenylethanolamine-N-methyltransferase mRNA induction via GRs was also differentially affected by the splice variants. Another type is receptor specificity: responses mediated by the N-terminal part of the MR, but not the GR, were augmented by SRC-1e at synergizing response elements. SRC fragment SRC(988-1240) by the MR but not the GR N-terminal fragment in a 1-hybrid assay. The last type, for GRs, is ligand dependence. Due to effects on partial agonism of RU486-activated GRs, different ratios of SRC-1a and 1e can lead to large differences in the extent of antagonism of RU486 on GR-mediated transcription. Furthermore, we show that SRC-1e but not SRC-1a mRNA expression was regulated in the pituitary by corticosterone. We conclude that the cellular differences in SRC-1a to SRC-1e ratio demonstrated in vivo might be involved in cell-specific responses to corticosteroids in a promoter- and ligand-dependent way.